2005
DOI: 10.2105/ajph.2004.044560
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Recurrent Trauma Among Young Black Men: Traumatic Stress, Substance Use, and the “Code of the Street”

Abstract: Recurrent interpersonal violence is a major cause of death and disability among young Black men. Quantitative studies have uncovered factors associated with reinjury, but little is known about how these factors work together. We interviewed young Black male victims to understand their experience of violence. Qualitative analysis of their narratives revealed how their struggle to reestablish safety shaped their response to injury. Aspects of the "code of the street" (including the need for respect) and lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
211
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 254 publications
(233 citation statements)
references
References 26 publications
16
211
0
Order By: Relevance
“…[1][2][3][4] Current study findings are also consistent with substantial research indicating that violence experienced during adolescence increases risk for involvement in high risk behaviors such as criminal activity/deviance, 3,31 drug and alcohol use, 14,22,23 and violence perpetration, [32][33][34] as well as a number of negative health and psychosocial effects 19,20,22,35 in adulthood. More specifically, a number of studies focusing on street violence involvement as well as violence perpetrated against an intimate partner have highlighted men's previous experiences as victims to be a significant factor driving these forms of violence perpetration later in life.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…[1][2][3][4] Current study findings are also consistent with substantial research indicating that violence experienced during adolescence increases risk for involvement in high risk behaviors such as criminal activity/deviance, 3,31 drug and alcohol use, 14,22,23 and violence perpetration, [32][33][34] as well as a number of negative health and psychosocial effects 19,20,22,35 in adulthood. More specifically, a number of studies focusing on street violence involvement as well as violence perpetrated against an intimate partner have highlighted men's previous experiences as victims to be a significant factor driving these forms of violence perpetration later in life.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, this association remained significant after accounting for childhood experiences of victimization. While previous work has documented the multitude of negative health effects from early experiences of victimization (e.g., poor mental health outcomes), [16][17][18][19][20][21] these findings highlight the long-term impact specific to adolescent victimization beyond young adulthood, and contribution to violence perpetration in low income Black communities.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The data used for this paper were collected as part of 20,24 This longitudinal qualitative analysis was undertaken to investigate significant individual and environmental risk factors associated with repeat ED visits for violence among young Black men. In addition, the study aimed to investigate how young Black men accessed continued health care for their traumatic injuries (both physical and psychological) following discharge from the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative studies on recurrent trauma among young Black men found that harassment and racial profiling by the police were significant sources of trauma and stress. 20 Researchers found that young Black men expressed a lack of faith in the police and that they could not depend on the police to protect them from danger.…”
Section: Death In Custody Reporting Actmentioning
confidence: 99%